Integration of Language in The Novel “Orang Orang Ordinaire” By Andrea Hirata (Sociolinguistic Studies) (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study aims to examine language integration in the novel Ordinary People by Andrea Hirata (Sociolinguistic Studies) so that language users in general better understand what is meant by language integration and how the form of language integration is contained in the novel orang-orang biasa by Andrea Hirata. Andrea Hirata is known as a writer who is rich in linguistic and symbolic exploration in his work, so this novel is an interesting object to analyze in terms of language. In the novel, the author combines standard Indonesian with a variety of regional languages, local idioms, and everyday expressions used by characters from the lower social class. Language integration not only represents the social background of the characters, but also serves as a means to reinforce the irony, social criticism, and humorous nuances that are typical of Andrea Hirata's writing style. A qualitative approach is used in this study, with the content analysis method as a tool to uncover the layers of language meaning hidden behind dialogues, narratives, and character descriptions. The results of the analysis show that there are four forms of language integration. The language integration found in Andrea Hirata's novel of orang-orang biasa is a form of audio integration, visual integration, direct translation integration, and concept translation integration. The most dominant form of integration in Andrea Hirata's novel orangorang biasa is the language absorbed from English.